2003
DOI: 10.1074/jbc.c300022200
|View full text |Cite
|
Sign up to set email alerts
|

Nevirapine Resistance Mutation at Codon 181 of the HIV-1 Reverse Transcriptase Confers Stavudine Resistance by Increasing Nucleotide Substrate Discrimination and Phosphorolytic Activity

Abstract: Recombinant HIV-1 reverse transcriptase (RT) carrying non-nucleoside inhibitors (NNRTIs) resistance mutation at codon 181 showed reduced incorporation and high efficiency of phosphorolytic removal of stavudine, a nucleoside RT inhibitor. These results reveal a new mechanism for cross-resistance between different classes of HIV-1 RT inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Moreover, defined combinations of mutations (thymidine analog mutations) primarily selected for by a single thymidine analog, such as zidovudine (AZT), have been linked to reduced susceptibilities to other compounds with similar structures (22). Recently, interclass resistance based on a point mutation in RT has been reported (2,3). However, multidrug resistance is commonly used to refer to a broad spectrum of resistance to antiretroviral drugs.…”
mentioning
confidence: 99%
“…Moreover, defined combinations of mutations (thymidine analog mutations) primarily selected for by a single thymidine analog, such as zidovudine (AZT), have been linked to reduced susceptibilities to other compounds with similar structures (22). Recently, interclass resistance based on a point mutation in RT has been reported (2,3). However, multidrug resistance is commonly used to refer to a broad spectrum of resistance to antiretroviral drugs.…”
mentioning
confidence: 99%
“…It is typical that mutations selected after treatment with NRTIs or NNRTIs are resistant to several compounds within the same class of drugs; however, it is quite rare for mutations to confer resistance to different classes of compounds. Among the described dual NRTI and NNRTI resistance mutations located in the NNRTI BP and deoxynucleoside triphosphate (dNTP) BP, it has been reported that Y181I/C is cross-resistant to NVP and 2,3-didehydro-2,3-dideoxythymidine (d4T) (4,5), G190S/A/E is crossresistant to NVP, d4T, and AZT (39), and Q145M, a very rare mutation in the dNTP BP that is selected in highly treated patients, is cross-resistant to both NRTIs and NNRTIs (41).…”
mentioning
confidence: 99%
“…Desensitization is apparently due to neither increased discrimination nor enhanced DEC formation, but rather to reduced ATP binding, resulting in a less efficient ATP-mediated unblocking reaction [175]. Finally, mutation Y181I alone confers cross-resistance to d4T only, by increasing both discrimination against d4TTP and its ATP-dependent excision [176]. Viruses highly resistant to AZT isolated from patients undergoing long-term antiretroviral therapy contain, in addition to the usual set of AZT resistance mutations, a deletion at position 67 (named the D67 complex) [89].…”
Section: Synergy Between Nrtis and Nnrtismentioning
confidence: 95%
“…In addition, there is some evidence that the anti-HCV drug ribavirin is an RNA virus mutagen [258][259][260]. 176 V. Vivet-Boudou et al Nucleoside and nucleotide inhibitors of HIV-1 replication Figure 5. Inhibition of reverse transcription by 'delayed polymerization arrest' .…”
Section: New Classes Of Anti-hiv Nucleoside Analoguesmentioning
confidence: 97%